Preparation method of adhesive-free solvent-free UV-cured wafer grinding protective film suitable for large-particle-size wafers with bumps / copper cylinders / solder balls
By using polyurethane acrylate main polymer containing amino groups and epoxy groups, combined with other functional agents, a single-layer UV curing protective film with high elongation of break and strong adhesion was prepared, and large-size hot-sized stainless steel ball wafers were solved The problem of peeling off the protective film during grinding improves the efficiency and yield of the wafer manufacturing process.
Patent Information
- Application Number
- CN202411698397.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
AI Technical Summary
When processing large-particle-sized stainless steel ball wafers, the traditional UV cured wafer abrasive protective film is difficult to meet high adhesion, good elasticity and wear resistance, and glue is easily retained during the peeling process, affecting the wafer quality and finished product rate. .
Using polyurethane acrylate containing amino groups and epoxy groups as the main polymer, a single-layer protective film was prepared through UV curing environmentally friendly process, combining toughening agents, photoinitiators, nanofillers, adhesion accelerators and defoamers, designed High elongation of break and strong adhesion to avoid leaving glue.
The effect of leaving no glue during the peeling process is achieved, ensuring the cleanliness of the wafer surface and the smooth progress of the subsequent process, meeting the special needs of large-particle wafer grinding, and improving efficiency and yield.
Abstract
Description
Technical Field
[0001] The invention provides a method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls, and relates to the technical field of special-effect film structures. Background Art
[0002] Wafer grinding is a crucial step in the semiconductor manufacturing process. Its purpose is to remove the material layer on the surface of the wafer by physical or chemical means to achieve the preset thickness and flatness requirements. In this process, the wafer surface is extremely susceptible to contaminants such as impurities, dust and debris generated during the grinding process, which leads to a decline in wafer quality and even the scrapping of the entire batch of products. Therefore, how to effectively protect the wafer surface and avoid contamination and damage during the grinding process has become a major problem in wafer grinding technology. Wafer grinding protective film came into being in this context. It can fit tightly on the surface of the wafer to form a solid protective barrier, effectively blocking contaminants and debris during the grinding process, while reducing mechanical damage to the wafer surface during the grinding process. With the continuous reduction of semiconductor process nodes, the difficulty of wafer grinding is increasing, and the performance requirements for grinding protective films are also getting higher and higher. Therefore, the development of high-performance and multifunctional wafer grinding protective films is of great significance to improving the quality of semiconductor products, reducing production costs, and promoting the development of semiconductor technology. At present, there are many types of wafer grinding protective films on the market, which can be divided into many types according to their structure, materials and application fields. Among them, UV-curing wafer grinding protective film has been widely used in the field of semiconductor manufacturing due to its high efficiency and environmental protection. UV curing technology uses ultraviolet light to trigger a chemical reaction, so that the liquid material is quickly solidified to form a solid protective film layer. This technology not only has a fast curing speed and low energy consumption, but is also environmentally friendly and pollution-free, meeting the requirements of green production in the semiconductor industry. However, despite the significant progress in technology and application of UV-curing wafer grinding protective film, there are still many challenges in processing large-particle solder ball wafers. Large-particle solder ball wafers have high surface undulations and high unevenness, which puts higher requirements on the performance of the protective film. Traditional protective films may not be able to fully meet these requirements, resulting in problems such as protective film shedding and excessive wear during the grinding process, and may even affect the quality and yield of the wafer surface. Large-particle solder ball wafers have higher requirements for grinding protective films due to their special surface structure and mechanical properties. Specifically, it mainly includes the following aspects: the raised structure formed by large-size solder balls on the wafer surface requires the protective film to have stronger adhesion to ensure that it can fit closely to the wafer surface during the grinding process to prevent grinding fluid and debris from penetrating into the gap between the solder balls and the wafer. If the adhesion is insufficient, the protective film may fall off or tear due to stress concentration, affecting the protective effect; large solder balls will produce greater stress and deformation during the grinding process, requiring the protective film to have good elastic properties to absorb and disperse these stresses and prevent cracks or ripples on the wafer surface.If the elasticity is insufficient, the protective film may fail under stress and cannot continue to play a protective role; since the large solder ball size increases the difficulty and time of grinding, the protective film needs to have higher wear resistance to ensure that its protective performance can be maintained during the long grinding process. If the wear resistance is insufficient, the protective film may lose its protective effect due to excessive wear and may even damage the wafer surface. However, while the protective film with greater adhesion brings the above advantages, it also brings new challenges-the problem of glue residue when tearing off the protective film. Specifically, due to the presence of large-sized solder balls, many uneven areas are formed on the surface of the wafer, which increases the contact area between the protective film and the wafer surface in these areas, and the adhesion is also enhanced accordingly. When the grinding is completed and the protective film is tried to be torn off, these areas with strong adhesion can easily cause the protective film to be unable to be completely and cleanly peeled off due to problems such as angle and strength, leaving residual glue on the surface of the wafer. The harm of the residual glue problem is self-evident. First, the residual glue will affect the cleanliness and flatness of the wafer surface, causing trouble for subsequent semiconductor manufacturing processes. Secondly, the residual glue may introduce new sources of pollution, resulting in a decrease in wafer quality. Finally, if the residual glue is not handled properly, it may also cause scratches or damage to the wafer surface, further reducing the yield rate. There is currently no perfect solution to the problem of residual glue when the protective film of large-size solder ball wafers is torn off. Existing technical means mainly focus on optimizing the formula and manufacturing process of the protective film in order to reduce the rate of residual glue during the peeling process. However, these methods often require compromises between adhesion, elasticity and wear resistance, and it is difficult to meet all performance requirements. In addition, in terms of the preparation method of the protective film, no one currently uses UV curing environmentally friendly processes. This field urgently needs to develop corresponding processes to meet application and environmental protection needs. Summary of the invention
[0003] To solve the above problems, the specific solutions provided by the present invention are as follows: A method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls, comprising the following steps: (1) Mix and stir the components in the adhesive layer evenly; (2) The obtained material is evenly coated on the surface of the base film; (3) UV curing; (4) A release film is attached to the surface of the UV-cured adhesive layer to obtain a wafer grinding protective film.
[0004] Preferably, the coating comprises roller coating, spin coating, dip coating or spray coating.
[0005] Preferably, the roller coating is 1-10 m / min, and the roller distance is 20-600 μm; the spin coating: the rotation speed range is 1000-5000 rpm, and the time is 30-120 seconds; the dip coating: the dip coating speed is 1-10 mm / s, and the pulling speed is adjustable; the spray coating: the spray pressure is 0.2-0.6 MPa, and the spray distance is 15-30 cm.
[0006] Preferably, for the UV curing, the UV light source power is 20mW-200mW, and the curing time is 20-60 seconds.
[0007] Preferably, the thickness of the obtained protective film adhesive layer is controlled within the range of 20-600 μm, and the thickness of the obtained protective film is controlled within the range of 100-700 μm.
[0008] Preferably, pre-curing may be performed before UV curing, wherein the pre-curing temperature ranges from 50 to 80° C. and the time is 10 to 20 minutes.
[0009] The protective film comprises a substrate, a glue layer and a release film, wherein the glue layer comprises a main polymer, a toughening agent, a photoinitiator, a nanofiller, an adhesion promoter, a leveling agent and a defoaming agent; Wherein, the main polymer is prepared by the following steps: S1. Preparation of a polyurethane prepolymer containing an amino group: adding a diol and a diamine to a reaction kettle and heating the mixture, slowly dropping a diisocyanate under stirring, and adding a catalyst to react. When the NCO content reaches a predetermined value, cooling the reaction mixture to room temperature; S2. Introducing epoxy groups: heating the obtained mixture, slowly adding epichlorohydrin (ECH) and triethylamine (TEA) under stirring to react, and cooling to room temperature after the reaction is completed; S3. Capping and acrylate esterification: Add hydroquinone (HQ) to the obtained mixture and heat it. Slowly add hydroxyethyl acrylate (HEA) dropwise under stirring to react. After the reaction is completed, cool it to room temperature and separate the product.
[0010] Preferably, the diol in S1 includes one or more of polyethylene glycol, polypropylene glycol (PPG), polytetramethylene glycol (PTMEG), and 1,4-butanediol (BDO).
[0011] Preferably, the diamine in S1 includes ethylenediamine or hexamethylenediamine.
[0012] Preferably, the diisocyanate in S1 includes toluene diisocyanate or hexamethylene diisocyanate.
[0013] Preferably, the molar ratio of the diamine, diol and diisocyanate in S1 is (2.5-4):1:(3-4.5).
[0014] Preferably, the catalyst in S1 is dibutyltin dilaurate (DBTDL), and the amount used is 0.1-0.3wt% of the total mass of the diamine, diol and diisocyanate.
[0015] Preferably, the heating in S1 is heated to a temperature of 60-80° C., the reaction time is 2-4 hours, and the predetermined value of the NCO content is 30-40%.
[0016] Preferably, the heating in step S2 is heated to a temperature of 40-60° C., the amount of triethylamine used is 0.3-0.5wt% of the total mass of the reactants, the molar ratio of epichlorohydrin to the diamine in step S1 is 1:(3-5), and the reaction time is 2-4h.
[0017] Preferably, the heating in S3 is heated to a temperature of 50-70°C, the reaction time is 2-4h, the amount of hydroquinone (HQ) is 0.3-0.5wt% of the mass of the mixture, the molar ratio of hydroxyethyl acrylate (HEA) to the diisocyanate in step S1 is 1:(2-6), and the molecular weight of the obtained product is 5000-15000.
[0018] Preferably, the separation of the product in S3 comprises: using ethyl acetate or toluene as a solvent for extraction, specifically: transferring the reaction mixture to a separatory funnel, adding an extraction solvent, thoroughly oscillating and mixing, standing in an environment of 10°C to separate the layers, retaining the product layer, removing the solvent layer, and repeating the extraction 2-3 times until the solvent layer is almost colorless.
[0019] Preferably, the components in the protective film include, by mass, 70-80 parts of the main polymer, 1-3 parts of the toughening agent, 3-5 parts of the photoinitiator, 5-8 parts of the nanofiller, 1-3 parts of the adhesion promoter, 0.5-1 parts of the leveling agent, and 0.5-1 parts of the defoaming agent.
[0020] Preferably, the toughening agent includes one or more of polydimethylsiloxane toughening agent, polyether toughening agent, and polyester toughening agent; further preferably, the toughening agent includes one or more of polydimethylsiloxane toughening agent BYK-410, TEGOGlide 410, and EFKA 3777.
[0021] Preferably, the photoinitiator includes one or two of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 2-hydroxy-2-methyl-1-phenyl-1-propanone, and more preferably includes one or more of Irgacure 184, Irgacure TPO and Darocur1173.
[0022] Preferably, the nanofiller includes one or both of nanosilica or nanoclay; more preferably, the nanosilica includes one or both of Aerosil 200, SiO2 nanopowder, and NanoSilica, and the nanoclay includes one or both of Laponite XLS and Bentone 38.
[0023] Preferably, the adhesion promoter includes one or more of titanate AP100, Adherant ADP promoter or BYK-4510 adhesion promoter, and further includes one or more of Ken-React AP100, Titanate AP-10, ADP-1 and ADP-2.
[0024] Preferably, the leveling agent includes one or two of polyacrylate leveling agents and acrylic leveling aids, and further includes one or more of BYK-333, TEGO Flow 300, and EFKA 3000.
[0025] Preferably, the defoaming agent includes one or more of polydimethylsiloxane defoaming agent, silicone defoaming aid, and silicone oil defoaming agent, and further includes one or more of BYK-052, TEGO Airex 900, EFKA 2722, Silcolapse432, and Silcolapse 7075.
[0026] The beneficial effects of the present invention are as follows: The present invention adopts a UV curing environmentally friendly process to prepare a wafer grinding protective film, and the present invention prepares a new main polymer: polyurethane acrylate (PUA) containing amino groups and epoxy groups (molecular weight 5000-15000, viscous liquid at room temperature), wherein the preparation method thereof is as follows: preparing a polyurethane prepolymer containing amino groups: the amino groups of the polyamine react with diisocyanate to form a urea bond connection, and at the same time the polyol reacts with diisocyanate to form a polyurethane segment; introducing epoxy groups: since the amino groups are nucleophilic, they can undergo a ring-opening reaction with the epoxy groups in epichlorohydrin, thereby introducing epoxy groups into the polyurethane segment; end-capping and acrylate esterification: the hydroxyl groups in hydroxyethyl acrylate can react with the remaining isocyanate groups in the polyurethane prepolymer to achieve end-capping; at the same time, its acrylate groups can be retained to provide cross-linking points for subsequent UV curing. The polymer cooperates with other components in the film to achieve the following effects: High elongation at break: Ensure that the protective film will not break due to excessive stretching during the peeling process, while maintaining a close fit to the wafer surface, effectively preventing the infiltration of grinding fluid and debris. This high elongation at break design is particularly suitable for large-particle wafers with bumps / copper pillars / tin balls, because large solder balls will produce greater stress and deformation during the grinding process. Protective films with high elongation at break can better adapt to these changes and avoid damage to the wafer surface. No adhesive residue: Avoids the residual problem that may be caused by the traditional adhesive layer. During the UV curing process, the protective film can be completely cured and form a tight and stable bond with the wafer surface. No adhesive residue will be left when peeling, ensuring the cleanliness of the wafer surface and the smooth progress of subsequent processes. Single-layer structure: The single-layer adhesive layer structure design is adopted without an adhesive layer, which reduces the complexity of the traditional multi-layer protective film structure, reduces production costs and the difficulty of waste disposal, and avoids residual adhesive. At the same time, the single-layer structure also avoids problems such as interlayer peeling and bubbles that may occur in the multi-layer structure, and improves the overall performance and stability of the protective film. Strong adhesion: The adhesion between the protective film and the wafer surface is enhanced by adding an adhesion promoter. This strong adhesion ensures that the protective film can fit tightly to the wafer surface during the grinding process, preventing the intrusion of grinding fluid and debris, and also helps the protective film to be cleanly and completely detached from the wafer surface when peeling.
[0027] In summary, the non-adhesive and solvent-free UV-curable wafer grinding protective film suitable for large-particle wafers with bumps / copper pillars / tin balls provided by the present invention has excellent performance in terms of elongation at break, adhesion, and no adhesive retention. It can meet the special needs in the grinding process of large-particle wafers with bumps / copper pillars / tin balls, and improve the efficiency and yield of the wafer manufacturing process. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0030] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0031] Preparation Example Preparation of main polymer: S1. Preparation of a polyurethane prepolymer containing an amino group: adding a diol and a diamine to a reaction kettle and heating the mixture, slowly dropping a diisocyanate under stirring, and adding a catalyst to react. When the NCO content reaches a predetermined value, cooling the reaction mixture to room temperature; S2. Introducing epoxy groups: heating the obtained mixture, slowly adding epichlorohydrin (ECH) and triethylamine (TEA) under stirring to react, and cooling to room temperature after the reaction is completed; S3. Capping and acrylate esterification: Add hydroquinone (HQ) to the obtained mixture and heat it. Slowly add hydroxyethyl acrylate (HEA) dropwise under stirring to react. After the reaction is completed, cool it to room temperature and separate the product.
[0032] The diol described in S1 includes one or more of polyethylene glycol, polypropylene glycol (PPG), polytetramethylene glycol (PTMEG), and 1,4-butanediol (BDO).
[0033] The diamine described in S1 includes ethylenediamine or hexamethylenediamine.
[0034] The diisocyanate in S1 includes toluene diisocyanate or hexamethylene diisocyanate.
[0035] The molar ratio of diamine, diol and diisocyanate in S1 is (2.5-4):1:(3-4.5).
[0036] The catalyst in S1 is dibutyltin dilaurate (DBTDL), and the amount used is 0.1-0.3wt% of the total mass of diamine, diol and diisocyanate.
[0037] The heating in S1 is heated to a temperature of 60-80°C, the reaction time is 2-4h, and the predetermined value of the NCO content is 30-40%.
[0038] The heating in step S2 is heated to a temperature of 40-60° C., the amount of triethylamine used is 0.3-0.5wt% of the total mass of the reactants, the molar ratio of epichlorohydrin to the diamine in step S1 is 1:(3-5), and the reaction time is 2-4h.
[0039] The heating in step S3 is heated to a temperature of 50-70°C, the reaction time is 2-4h, the amount of hydroquinone (HQ) is 0.3-0.5wt% of the mass of the mixture, the molar ratio of hydroxyethyl acrylate (HEA) to the diisocyanate in step S1 is 1:(2-6), and the molecular weight of the obtained product is 5000-15000.
[0040] The separation of the product described in S3 includes: using ethyl acetate or toluene as a solvent for extraction, specifically: transferring the reaction mixture to a separatory funnel, adding an extraction solvent, fully oscillating and mixing, standing in an environment of 10°C to separate the layers, retaining the product layer, removing the solvent layer, and repeating the extraction 2-3 times until the solvent layer is almost colorless.
[0041] Preparation Example 1 Preparation of main polymer: S1. Preparation of a polyurethane prepolymer containing an amino group: adding a diol and a diamine to a reaction kettle and heating the mixture, slowly dropping a diisocyanate under stirring, and adding a catalyst to react. When the NCO content reaches a predetermined value, cooling the reaction mixture to room temperature; S2. Introducing epoxy groups: heating the obtained mixture, slowly adding epichlorohydrin (ECH) and triethylamine (TEA) under stirring to react, and cooling to room temperature after the reaction is completed; S3. Capping and acrylate esterification: Add hydroquinone (HQ) to the obtained mixture and heat it. Slowly add hydroxyethyl acrylate (HEA) dropwise under stirring to react. After the reaction is completed, cool it to room temperature and separate the product.
[0042] The diol described in S1 includes polyethylene glycol.
[0043] The diamine described in S1 includes ethylenediamine.
[0044] The diisocyanate described in S1 includes toluene diisocyanate.
[0045] The molar ratio of the diamine, diol and diisocyanate in S1 is 4:1:4.5.
[0046] The catalyst in S1 is dibutyltin dilaurate (DBTDL), and the amount used is 0.3wt% of the total mass of diamine, diol and diisocyanate.
[0047] The heating in S1 is heated to a temperature of 80° C., the reaction time is 2-4 hours, and the predetermined value of the NCO content is 40%.
[0048] The heating in step S2 is heated to a temperature of 60° C., the amount of triethylamine used is 0.5wt% of the total mass of the reactants, the molar ratio of epichlorohydrin to the diamine in step S1 is 1:5, and the reaction time is 4h.
[0049] The heating in step S3 is heated to a temperature of 70° C. The reaction time is 2 hours. The amount of hydroquinone (HQ) is 0.5wt% of the mass of the mixture. The molar ratio of hydroxyethyl acrylate (HEA) to the diisocyanate in step S1 is 1:6. The molecular weight of the obtained product is 5000-15000.
[0050] The product separation step S3 comprises: using ethyl acetate as a solvent for extraction, specifically: transferring the reaction mixture to a separatory funnel, adding an extraction solvent, thoroughly shaking and mixing, standing in an environment of 10°C to separate the layers, retaining the product layer, removing the solvent layer, and repeating the extraction three times until the solvent layer is almost colorless.
[0051] Preparation Example 2 Preparation of main polymer: S1. Preparation of a polyurethane prepolymer containing an amino group: adding a diol and a diamine to a reaction kettle and heating the mixture, slowly dropping a diisocyanate under stirring, and adding a catalyst to react. When the NCO content reaches a predetermined value, cooling the reaction mixture to room temperature; S2. Introducing epoxy groups: heating the obtained mixture, slowly adding epichlorohydrin (ECH) and triethylamine (TEA) under stirring to react, and cooling to room temperature after the reaction is completed; S3. Capping and acrylate esterification: Add hydroquinone (HQ) to the obtained mixture and heat it. Slowly add hydroxyethyl acrylate (HEA) dropwise under stirring to react. After the reaction is completed, cool it to room temperature and separate the product.
[0052] The diol described in S1 includes polypropylene glycol.
[0053] The diamine described in S1 includes ethylenediamine.
[0054] The diisocyanate described in S1 includes toluene diisocyanate.
[0055] The molar ratio of the diamine, diol and diisocyanate in S1 is 3:1:4.
[0056] The catalyst in S1 is dibutyltin dilaurate (DBTDL), and the amount used is 0.2wt% of the total mass of diamine, diol and diisocyanate.
[0057] The heating in S1 is heated to a temperature of 60° C., the reaction time is 2-4 hours, and the predetermined value of the NCO content is 40%.
[0058] The heating in step S2 is heated to a temperature of 40° C. The amount of triethylamine used is 0.3wt% of the total mass of the reactants. The molar ratio of epichlorohydrin to the diamine in step S1 is 1:4. The reaction time is 4h.
[0059] The heating in step S3 is heated to a temperature of 50° C. The reaction time is 4 hours. The amount of hydroquinone (HQ) is 0.3wt% of the mass of the mixture. The molar ratio of hydroxyethyl acrylate (HEA) to the diisocyanate in step S1 is 1:4. The molecular weight of the obtained product is 5000-15000.
[0060] The product separation step S3 comprises: using ethyl acetate as a solvent for extraction, specifically: transferring the reaction mixture to a separatory funnel, adding an extraction solvent, thoroughly shaking and mixing, standing in an environment of 10°C to separate the layers, retaining the product layer, removing the solvent layer, and repeating the extraction three times until the solvent layer is almost colorless.
[0061] Comparative Preparation Example 1 Preparation of main polymer (without introduction of amino and epoxy groups): S1, adding diol to a reaction kettle and heating it, slowly dropping diisocyanate under stirring, and adding a catalyst to react, and when the NCO content reaches a predetermined value, cooling the reaction mixture to room temperature; S2. Capping and acrylate esterification: Add hydroquinone (HQ) to the obtained mixture and heat it. Slowly add hydroxyethyl acrylate (HEA) dropwise under stirring to react. After the reaction is completed, cool it to room temperature and separate the product.
[0062] The diol described in S1 includes polypropylene glycol.
[0063] The diisocyanate described in S1 includes toluene diisocyanate.
[0064] The molar ratio of diol to diisocyanate in S1 is 1:4.
[0065] The catalyst in S1 is dibutyltin dilaurate (DBTDL), and the amount used is 0.2wt% of the total mass of diol and diisocyanate.
[0066] The heating in S1 is heated to a temperature of 60° C., the reaction time is 2-4 hours, and the predetermined value of the NCO content is 40%.
[0067] The heating in step S2 is heated to a temperature of 50° C. The reaction time is 4 hours. The amount of hydroquinone (HQ) is 0.3wt% of the mass of the mixture. The molar ratio of hydroxyethyl acrylate (HEA) to the diisocyanate in step S1 is 1:4. The molecular weight of the obtained product is 4000-14000.
[0068] The product separation step S3 comprises: using ethyl acetate as a solvent for extraction, specifically: transferring the reaction mixture to a separatory funnel, adding an extraction solvent, thoroughly shaking and mixing, standing in an environment of 10°C to separate the layers, retaining the product layer, removing the solvent layer, and repeating the extraction three times until the solvent layer is almost colorless.
[0069] Comparative Preparation Example 2 Preparation of main polymer (without introduction of epoxy group): S1. Preparation of a polyurethane prepolymer containing an amino group: adding a diol and a diamine to a reaction kettle and heating the mixture, slowly dropping a diisocyanate under stirring, and adding a catalyst to react. When the NCO content reaches a predetermined value, cooling the reaction mixture to room temperature; S2. Capping and acrylate esterification: Add hydroquinone (HQ) to the obtained mixture and heat it. Slowly add hydroxyethyl acrylate (HEA) dropwise under stirring to react. After the reaction is completed, cool it to room temperature and separate the product.
[0070] The diol described in S1 includes polypropylene glycol.
[0071] The diamine described in S1 includes ethylenediamine.
[0072] The diisocyanate described in S1 includes toluene diisocyanate.
[0073] The molar ratio of the diamine, diol and diisocyanate in S1 is 2:1:4.
[0074] The catalyst in S1 is dibutyltin dilaurate (DBTDL), and the amount used is 0.2wt% of the total mass of diamine, diol and diisocyanate.
[0075] The heating in S1 is heated to a temperature of 60° C., the reaction time is 2-4 hours, and the predetermined value of the NCO content is 40%.
[0076] The heating in step S2 is heated to a temperature of 50° C. The reaction time is 4 hours. The amount of hydroquinone (HQ) is 0.3wt% of the mass of the mixture. The molar ratio of hydroxyethyl acrylate (HEA) to the diisocyanate in step S1 is 1:4. The molecular weight of the obtained product is 5000-15000.
[0077] The product separation step S3 comprises: using ethyl acetate as a solvent for extraction, specifically: transferring the reaction mixture to a separatory funnel, adding an extraction solvent, thoroughly shaking and mixing, standing in an environment of 10°C to separate the layers, retaining the product layer, removing the solvent layer, and repeating the extraction three times until the solvent layer is almost colorless.
[0078] The preparation process of the protective film in the following embodiment is: a preparation method of a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-particle wafers of bumps / copper pillars / tin balls: (1) Mix and stir the components in the adhesive layer evenly; (2) The obtained material is evenly coated on the surface of the base film (10 μm thick TPU base film); (3) UV curing; (4) A release film is attached to the surface of the UV-cured adhesive layer to obtain a wafer grinding protective film.
[0079] The coating includes spin coating, dip coating or spray coating.
[0080] The spin coating was performed at a rotation speed of 2000 rpm and a time of 30 seconds.
[0081] The UV curing has a UV light source power of 4000 W and a curing time of 30 seconds.
[0082] The thickness of the obtained protective film was controlled at 60 μm.
[0083] Example 1 A non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers with bumps / copper pillars / tin balls (with a relatively low content of main polymer) The components in the protective film include, by weight: 70 parts of the main polymer obtained in Preparation Example 1, 3 parts of a toughening agent, 5 parts of a photoinitiator, 8 parts of a nanofiller, 3 parts of an adhesion promoter, 1 part of a leveling agent, and 1 part of a defoaming agent.
[0084] The toughening agent includes polydimethylsiloxane toughening agent BYK-410.
[0085] Photoinitiators include Irgacure TPO.
[0086] The nano filler includes nano silicon dioxide including Aerosil 200.
[0087] The adhesion promoter includes Ken-React AP100.
[0088] The leveling agent includes BYK-333.
[0089] The defoamer includes BYK-052.
[0090] Example 2 A non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers with bumps / copper pillars / tin balls (with a relatively high content of main polymer) The components in the protective film include, by weight: 80 parts of the main polymer obtained in Preparation Example 1, 1 part of a toughening agent, 3 parts of a photoinitiator, 5 parts of a nanofiller, 1 part of an adhesion promoter, 0.5 parts of a leveling agent, and 0.5 parts of a defoaming agent.
[0091] The toughening agent includes polydimethylsiloxane toughening agent BYK-410.
[0092] Photoinitiators include Irgacure TPO.
[0093] The nano filler includes nano silicon dioxide including Aerosil 200.
[0094] The adhesion promoter includes Ken-React AP100.
[0095] The leveling agent includes BYK-333.
[0096] The defoamer includes BYK-052.
[0097] Example 3 A non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers with bumps / copper pillars / tin balls (compared with Example 2, the main polymer of Preparation Example 2 is used) The components in the protective film include, by weight: 80 parts of the main polymer obtained in Preparation Example 2, 1 part of a toughening agent, 3 parts of a photoinitiator, 5 parts of a nanofiller, 1 part of an adhesion promoter, 0.5 parts of a leveling agent, and 0.5 parts of a defoaming agent.
[0098] The toughening agent includes polydimethylsiloxane toughening agent BYK-410.
[0099] Photoinitiators include Irgacure TPO.
[0100] The nano filler includes nano silicon dioxide including Aerosil 200.
[0101] The adhesion promoter includes Ken-React AP100.
[0102] The leveling agent includes BYK-333.
[0103] The defoamer includes BYK-052.
[0104] The difference between Example 4 and Example 3 is that a pre-curing is performed before UV curing, the pre-curing temperature is 50° C., and the time is 20 minutes.
[0105] The difference between Comparative Example 1 and Example 3 is that the main polymer prepared in Comparative Preparation Example 1 (without the introduction of amino groups and epoxy groups) is used. The difference between Comparative Example 2 and Example 3 is that the main polymer prepared in Comparative Preparation Example 2 (without introducing epoxy groups) is used. Performance testing: The wafer solder balls used for testing are tin balls with a particle size of 200μm. Check the uniformity and integrity of the protective film. Clean the wafer surface to ensure that it is free of dust, oil, moisture and other contaminants. Remove the sample release film, evenly stick the sample on the wafer surface, ensure that there are no obvious bubbles between the sample and the wafer surface, heat the wafer to 60℃ to soften the adhesive layer, and test the adhesion after cooling to room temperature. After heat treatment at 80℃ for 30min and 200℃ for 60min, remove the protective film and observe the glue retention. The results are shown in Table 1. The adhesion can be reflected by measuring the force required to separate the protective film from the substrate during the stretching process through the tensile method. The elongation at break and tensile strength of all the above samples were tested with reference to the test method for tensile strength and elongation at break of adhesive tape in GB / T30776-2014. The tensile strength MD of all samples was higher than 52MPa, and the tensile strength TD was higher than 50MPa. The elongation at break is shown in Table 1 (the elongation at break and tensile strength are based on the break of the adhesive layer). Table 1 Sample performance test results sample Separation tensile force / peel strength N / m Elongation at break %MD Elongation at break %TD Is there any glue left after heat treatment at 80℃ for 30min? Is there any glue left after heat treatment at 200℃ for 30min? Example 1 66.3 443 431 no no Example 2 69.1 454 435 no no Example 3 69.8 457 433 no no Example 4 70.2 473 437 no no Comparative Example 1 55.7 358 344 no yes Comparative Example 2 55.3 289 267 yes yes It can be seen from the test results that the protective film containing a special main polymer provided by the present invention is applied to the surface of a wafer with a large solder ball particle size, which can achieve the effect of greatly improving the peel strength, and achieve the purpose of the present invention to avoid the problem of glue retention in the traditional structure protective film, and the resulting film product is uniform and complete, and the adsorption force meets the use requirements. Especially when the temperature is high during wafer grinding, the protective film provided by the present invention can still be kept without glue. At the same time, the tensile strength MD of all samples is higher than 52MPa, the tensile strength TD is higher than 50MPa, the elongation at break MD is higher than 339%, and the elongation at break TD is higher than 322%, which can meet the needs of the bump / copper pillar / solder ball large particle size wafer grinding process and improve the efficiency and yield rate of the wafer manufacturing process.
[0106] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0107] The present invention and its implementation methods are described above, which is not restrictive and is only one of the implementation methods of the present invention. The actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls, characterized in that: The following steps are involved: (1) Mix and stir the components in the adhesive layer evenly; (2) The obtained material is evenly coated on the surface of the base film; (3) UV curing; (4) A release film is attached to the surface of the UV-cured adhesive layer to obtain a wafer grinding protective film.
2. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 1, characterized in that: The coating includes roller coating, spin coating, dip coating or spray coating.
3. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 2, characterized in that: The roller coating is 1-10m / min, and the roller distance is 20-600μm; the spin coating: the rotation speed range is 1000-5000 rpm, and the time is 30-120 seconds; the dip coating: the dip coating speed is 1-10 mm / s, and the pulling speed is adjustable; the spray coating: the spray pressure is 0.2-0.6 MPa, and the spray distance is 15-30 cm.
4. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 1, characterized in that: The UV curing has a UV light source power of 20mW-200mW and a curing time of 20-60 seconds.
5. The method for preparing a wafer grinding protective film according to claim 1, characterized in that: The thickness of the obtained protective film adhesive layer is controlled within the range of 20-600 μm, and the thickness of the obtained protective film is controlled within the range of 100-700 μm.
6. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 1, characterized in that: The non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls comprises a substrate, a glue layer, and a release film, wherein the glue layer comprises a main polymer, a toughening agent, a photoinitiator, a nanofiller, an adhesion promoter, a leveling agent, and a defoaming agent; wherein the main polymer is prepared by the following steps: S1. Preparation of a polyurethane prepolymer containing an amino group: adding a diol and a diamine to a reaction kettle and heating the mixture, slowly dropping a diisocyanate under stirring, and adding a catalyst to react. When the NCO content reaches a predetermined value, cooling the reaction mixture to room temperature; S2. Introducing epoxy groups: heating the obtained mixture, slowly adding epichlorohydrin (ECH) and triethylamine (TEA) under stirring to react, and cooling to room temperature after the reaction is completed; S3. Capping and acrylate esterification: Add hydroquinone (HQ) to the obtained mixture and heat it. Slowly add hydroxyethyl acrylate (HEA) dropwise under stirring to react. After the reaction is completed, cool it to room temperature and separate the product.
7. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 6, characterized in that: The molar ratio of the diamine, diol and diisocyanate in S1 is (2.5-4):1:(3-4.5); the catalyst in S1 is dibutyltin dilaurate (DBTDL), and the amount used is 0.1-0.3wt% of the total mass of the diamine, diol and diisocyanate.
8. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 6, characterized in that: The heating in S1 is heated to a temperature of 60-80°C, the reaction time is 2-4h, and the predetermined value of the NCO content is 30-40%.
9. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 6, characterized in that: The heating in step S2 is heated to a temperature of 40-60° C., the amount of triethylamine used is 0.3-0.5wt% of the total mass of the reactants, the molar ratio of epichlorohydrin to the diamine in step S1 is 1:(3-5), and the reaction time is 2-4h.
10. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 6, characterized in that: The heating in step S3 is heated to a temperature of 50-70°C, the reaction time is 2-4h, the amount of hydroquinone (HQ) is 0.3-0.5wt% of the mass of the mixture, the molar ratio of hydroxyethyl acrylate (HEA) to the diisocyanate in step S1 is 1:(2-6), and the molecular weight of the obtained product is 5000-15000.
11. The method for preparing a non-adhesive solvent-free UV-curable wafer grinding protective film suitable for large-diameter wafers of bumps / copper pillars / tin balls according to claim 6, characterized in that: The separation of the product described in S3 includes: using ethyl acetate or toluene as a solvent for extraction, specifically: transferring the reaction mixture to a separatory funnel, adding an extraction solvent, fully oscillating and mixing, standing in an environment of 10°C to separate the layers, retaining the product layer, removing the solvent layer, and repeating the extraction 2-3 times until the solvent layer is almost colorless.